Case Report: Primary Aldosteronism and Subclinical Cushing Syndrome in a 49-Year-Old Woman With Hypertension Plus Hypokalaemia - Hu, Lihua; Ji, Wenjun; Guo, Meiyu; Yi, Tieci; Wang, Jie; Bao, Minghui; Gao, Yusi; Jin, Han; Lu, Difei; Ma, Wei; Han, Xiaoning; Li, Jianping; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Coexisting primary aldosteronism (PA) and subclinical Cushing’s syndrome (SCS) caused by bilateral adrenocortical adenomas have occasionally been reported. Precise diagnosis and treatment of the disease pose a challenge to clinicians due to its atypical clinical manifestations and laboratory findings. Case Summary: A 49-year-old woman was admitted to our hospital due to fatigue, increased nocturia and refractory hypertension. The patient had a history of severe left hydronephrosis six months prior. Laboratory examinations showed hypokalaemia (2.58mmol/L) and high urine potassium (71 mmol/24 h). Adrenal computed tomography (CT) showed bilateral adrenal masses. Undetectable ACTH and unsuppressed plasma cortisol levels by dexamethasone indicated ACTH-independent Cushing’s syndrome. Although the upright aldosterone-to-renin ratio (ARR) was 3.06 which did not exceed 3.7, elevated plasma aldosterone concentrations (PAC) with unsuppressed PAC after the captopril test still suggested PA. Adrenal venous sampling (AVS) without adrenocorticotropic hormone further revealed hypersecretion of aldosterone from the right side and no dominant side of cortisol secretion. A laparoscopic right adrenal tumor resection was performed. The pathological diagnosis was adrenocortical adenoma. After the operation, the supine and standing PAC were normalized; while the plasma cortisol levels postoperatively were still high and plasma renin was activated. The patient’s postoperative serum potassium and 24-hour urine potassium returned to normal without any pharmacological treatment. In addition, the patient’s blood pressure was controlled normally with irbesartan alone. Conclusion: Patients with refractory hypertension should be screened for the cause of secondary hypertension. AVS should be performed in patients in which PA is highly suspected to determine whether there is the option of surgical treatment. Moreover, patients with PA should be screened for hypercortisolism, which can contribute to a proper understanding of the AVS result.